Psychometric Evaluation of the Hypogonadism Impact of Symptoms Questionnaire Short Form (HIS-Q-SF). Issue 8 (1st August 2017) - Gelhorn, Heather L.; Roberts, Laurie J.; Khandelwal, Nikhil; Revicki, Dennis A.; DeRogatis, Leonard R.; Dobs, Adrian; Hepp, Zsolt; Miller, Michael G.
Abstract: Background: The Hypogonadism Impact of Symptoms Questionnaire Short Form (HIS-Q-SF) is a patient-reported outcome measurement designed to evaluate the symptoms of hypogonadism. The HIS-Q-SF is an abbreviated version including17 items from the original 28-item HIS-Q. Aim: To conduct item analyses and reduction, evaluate the psychometric properties of the HIS-Q-SF, and provide guidance on score interpretation. Methods: A 12-week observational longitudinal study of hypogonadal men was conducted as part of the original HIS-Q psychometric evaluation. Participants completed the original HIS-Q every 2 weeks. Blood samples were collected to evaluate testosterone levels. Participants completed the Aging Male's Symptoms Scale, the International Index of Erectile Function, the Short Form-12, and the PROMIS Sexual Activity, Satisfaction with Sex Life, Sleep Disturbance, and Applied Cognition Scales (baseline and weeks 6 and 12). Clinicians completed the Clinical Global Impression of Severity and Change scales and a clinical form. Main Outcome Measures: Item performance was evaluated using descriptive statistics and Rasch analyses. Reliability (internal consistency and test-retest), validity (concurrent and know groups), and responsiveness were assessed. Results: One hundred seventy-seven men participated (mean age = 54.1 years, range = 23–83). Similar to the full HIS-Q, the final abbreviated HIS-Q-SF instrument includes five domains (sexual, energy, sleep, cognition, and mood) with two sexual subdomains (libido and sexual function). For key domains, test-retest reliability was very good, and construct validity was good for all domains. Known-groups validity was demonstrated for all domain scores, subdomain scores, and total score based on the Clinical Global Impression–Severity. All domains and subdomains were responsive to change based on patient-rated anchor questions. Clinical Implications: The HIS-Q-SF could be a useful tool in clinical practice, epidemiologic studies, and other academic research settings. Strengths and Limitations: Careful consideration was given to the selection of the final HIS-Q-SF items based on quantitative data and clinical expert feedback. Overall, the reduced set of items demonstrated strong psychometric properties. Testosterone levels for the participating men were not as low as anticipated, which could have limited the ability to examine the relations between the HIS-Q-SF and testosterone levels. Further, the analyses used data collected through administration of the full HIS-Q, and future studies should administer the standalone HIS-Q-SF to replicate the psychometric analyses reported in the present study. Conclusion: Similar to the original HIS-Q, the HIS-Q-SF has evidence supporting reliability, validity, and responsiveness. The short form includes a smaller set of items that might be more suitable for use in clinical practice or academic research settings.